Peran dan Implementasi Regulasi Otoritas Jasa Keuangan dalam Pengawasan Tingkat Kesehatan Bank Muamalat - Rizal Ikhsan Rizkyawan; Lina Jamilah; Salma Suroyya (UPT Publikasi Ilmiah Unisba, 2025)
Abstract. This study analyses the role of the Financial Services Authority (OJK) in the health supervision of Bank Muamalat during 2013-2023 and evaluates the implementation of the regulations applied. OJK functions as an independent institution that maintains the stability of the national financial system, especially in the supervision of Indonesia's first Islamic bank, Bank Muamalat. The health of Bank Muamalat is an important indicator to assess the effectiveness of OJK supervision, especially amid economic challenges and the impact of the COVID-19 pandemic.The method used is normative juridical with a descriptive-analytical approach, as well as qualitative data analysis. Primary data includes Bank Muamalat's annual report, OJK regulations, and Islamic banking legal literature. The results showed that OJK plays a strategic role through risk-based supervision and regulations such as POJK Number 10/SEOJK.03/2014, which provides a comprehensive assessment framework.During the period, Bank Muamalat experienced fluctuations in the Risk Profile aspect, with the Non-Performing Financing (NPF) ratio decreasing significantly to 2.70% in 2023. Corporate governance showed improvement, although profitability still needs to be improved. In conclusion, OJK regulations contribute to the stability of Bank Muamalat, but there is still room for improvement in operational efficiency. Abstrak. Penelitian ini menganalisis peran Otoritas Jasa Keuangan (OJK) dalam pengawasan kesehatan Bank Muamalat selama 2013-2023 dan mengevaluasi implementasi regulasi yang diterapkan. OJK berfungsi sebagai lembaga independen yang menjaga stabilitas sistem keuangan nasional, terutama dalam pengawasan bank syariah pertama di Indonesia, Bank Muamalat. Kesehatan Bank Muamalat menjadi indikator penting untuk menilai efektivitas pengawasan OJK, terutama di tengah tantangan ekonomi dan dampak pandemi COVID-19. Metode yang digunakan adalah yuridis normatif dengan pendekatan deskriptif-analitis, serta analisis data kualitatif. Data primer meliputi laporan tahunan Bank Muamalat, peraturan OJK, dan literatur hukum perbankan syariah. Hasil penelitian menunjukkan OJK berperan strategis melalui pengawasan berbasis risiko dan regulasi seperti POJK Nomor 10/SEOJK.03/2014, yang memberikan kerangka penilaian komprehensif. Selama periode tersebut, Bank Muamalat mengalami fluktuasi dalam aspek Risk Profile, dengan rasio Non-Performing Financing (NPF) menurun signifikan hingga 2,70% pada 2023. Tata kelola perusahaan menunjukkan perbaikan, meskipun profitabilitas masih perlu ditingkatkan. Kesimpulannya, regulasi OJK berkontribusi pada stabilitas Bank Muamalat, namun masih ada ruang untuk perbaikan dalam efisiensi operasional. .